Experience in the treatment of patients with ACTH-independent macronodular bilateral adrenal hyperplasia - Aleksandr A. Lisitcyn; Vyacheslav P. Zemlyanoi; Sergei B. Shustov; Lyudmila I. Velikanova; Evgeniya M. Nesvit (Наука и инновации в медицине, 2023)
Aim to determine the optimal tactics for the examination and treatment of patients with macronadular bilateral adrenal hyperplasia.